IT encyclopaedia.com - Diwan, Parag (Ed.); Kaushik, Sanjay (Ed.); Suri, R K (Ed.) (New Delhi Pentagon, 2000)
IT Encyclopaedia is a ten volumes set and it cover the information about Fundamentals of information technology,Information system management, Software Engineers,computernetworks and ecommerce,multimedia system,graphical user interface Enterprise Resource
Contents: v.9. Information technology laws/ R K Suri, Parag Diwan and Shammi Kapoor
Keywords: Computers; Computer networks; Operating systems (Computers); Internet (Computers network); Information technology-Encyclopaedias and dictionaries; Software engineering; Computer networks; Information resources management; Electronic Commerce